2012
DOI: 10.1007/s10508-012-9995-6
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes Toward Transgendered Individuals Scale: Psychometric Properties

Abstract: Gay, lesbian, bisexual, and transgendered individuals are sexual and gender minorities subject to stigma in a heteronormative culture with binary gender role norms. Although much research has examined sexual stigma in the form of homophobia, or negative attitudes and reactions to homosexuals and homosexuality, little is known about the stigma experienced by transgendered individuals. Transgendered people are those whose gender identity (sense of oneself as a man or a woman) or gender expression (expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 34 publications
7
93
2
2
Order By: Relevance
“…The survey then included an adapted version of the Attitudes Towards Transgender Individuals Scale (ATTIS) (Walch, Ngamake, Francisco, Stitt, & Shingler, 2012), which uses a 5-point Likert scale to assess responses to 20 items. Adaptations to the scale primarily involved substituting the word 'people' for 'individuals' (so for example, "Transgender people should not be allowed to work with children" rather than "Transgender individuals should not be allowed to work with children").…”
Section: Methodsmentioning
confidence: 99%
“…The survey then included an adapted version of the Attitudes Towards Transgender Individuals Scale (ATTIS) (Walch, Ngamake, Francisco, Stitt, & Shingler, 2012), which uses a 5-point Likert scale to assess responses to 20 items. Adaptations to the scale primarily involved substituting the word 'people' for 'individuals' (so for example, "Transgender people should not be allowed to work with children" rather than "Transgender individuals should not be allowed to work with children").…”
Section: Methodsmentioning
confidence: 99%
“…The first of these was an adapted version of the Attitudes Towards Transgender Individuals Scale (ATTIS; Walch, Ngamake, Francisco, Stitt, & Shingler, 2012), which uses a 5-point Likert scale to assess -.780 3. I avoid transgender people whenever possible.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work consistently found that males were significantly more transphobic than females [7,10,18,20,27,34,35,37,42,43,52,53,56,58], and that male violations from societal gender norms evoke stronger negative reactions than female violations [38,39,49,58]. Baiocco et al [3] observed that females were reported to have a higher percentage of cross-gender best friends than males.…”
Section: Transphobia In Malesmentioning
confidence: 95%